Association of dietary fatty acid intake with hypertension in children and adolescents: evidence from the NHANES 2005–2018 - Li, Xiumin; Qi, Fengqin; Zhao, Zhihong; Ma, Jinbang (Frontiers in Pediatrics, 2023)
Aim This study aims to evaluate the association between dietary fatty acid intake and hypertension in children and adolescents. Methods This cross-sectional study used data of children and adolescents aged 8–17 years from the National Health and Nutrition Examination Survey (NHANES) 2005–2018. Dietary intake of total fat and fatty acid was evaluated via two 24-h dietary recall interviews. Multivariate logistic regression models were used to assess the association between fatty acid intake and hypertension, with odds ratios (ORs) and 95% confidence intervals (CIs) calculated. A subgroup analysis was conducted according to gender, age, and body mass index Z-score. Results This study included 13,330 subjects, of which 11,614 were non-hypertensive and 1,716 were hypertensive. Higher intake of total polyunsaturated fatty acids (PUFAs) was associated with significantly lower odds of hypertension (OR = 0.85, 95% CI: 0.74–0.97, P = 0.018). No significant associations were found between the density of total saturated fatty acid, monounsaturated fatty acids, and PUFAs and the odds of hypertension (all P > 0.05). Increased intake of omega-3 (OR = 0.82, 95% CI: 0.72–0.93, P = 0.002) and omega-6 (OR = 0.86, 95% CI: 0.75–0.98, P = 0.025) PUFAs, octadecatrienoic acid (OR = 0.82, 95% CI: 0.72–0.93, P = 0.003), and octadecadienoic acid (OR = 0.86, 95% CI: 0.75–0.98, P = 0.025) was associated with significantly lower odds of hypertension, and individuals with higher omega-6/omega-3 ratio had significantly higher odds of hypertension (OR = 1.09, 95% CI: 1.02–1.17, P = 0.025). The density of omega-3 PUFAs (OR = 0.86, 95% CI: 0.78–0.95, P = 0.004) and octadecatrienoic acid (OR = 0.87, 95% CI: 0.78–0.96, P = 0.006) was inversely associated with the odds of hypertension, and the omega-6/omega-3 ratio was positively associated with the odds of hypertension (OR = 1.09, 95% CI: 1.02–1.17, P = 0.012). Conclusion Total PUFA intake was negatively associated with the odds of hypertension in children and adolescents. Higher intake of omega-3 and omega-6 PUFAs, octadecatrienoic acid, and octadecadienoic acid, as well as density of omega-3 PUFAs and octadecatrienoic acid, was associated with lower odds of hypertension.